Influencia de la dosis de vacuna antiaftosa en la prueba de índice “C” de Lucam (1983)
Foot and mouth disease vaccines (25'636.170 doses) elaborated with virus processed in BHK 21 ceils in suspension cultures were tested by the Lucarn's "C" index (CO method.